2015
DOI: 10.1111/aas.12632
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Pleth Variability Index and oesophageal Doppler to predict fluid responsiveness

Abstract: PVI- and Doppler-based stroke volume optimisations agreed poorly, which did not affect the amount of fluid administered. None of the algorithms showed a good ability to predict fluid responsiveness. Our results do not support the fluid responsiveness concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
4
18
0
1
Order By: Relevance
“…From the remaining 146 patients, a preoperative urine sample had been obtained from 112. The results from the first half of this trial have been published elsewhere and show that the amount of fluid infused in the two groups was quite similar throughout the study (Bahlmann et al 2016 ).…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…From the remaining 146 patients, a preoperative urine sample had been obtained from 112. The results from the first half of this trial have been published elsewhere and show that the amount of fluid infused in the two groups was quite similar throughout the study (Bahlmann et al 2016 ).…”
Section: Methodssupporting
confidence: 53%
“…For the alternative method, a fluid bolus was given when the Pleth Variability Index exceeded 9%. Details of these measurements have been presented elsewhere (Bahlmann et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Primary outcome measures were the amount of colloid used for optimization of fluid status and the concordance between different methods for assessing preoperative dehydration. These results have been published elsewhere [ 9 , 10 ] and included the first half of the study cohort (75 patients). The present article focuses on clinical outcome in the whole cohort of 150 patients, as quantified by number of postoperative complications up to 30 days after surgery and length of hospital stay, both of which were designated as secondary outcome measures in the study protocol.…”
Section: Introductionmentioning
confidence: 99%
“…On contrary, Bahlmann et al [40] found pulse oximetric PVI-and esophageal Doppler-based stroke volume optimizations agreed poorly and did not affect the amount of fluid Table 4 Laboratory data reported at ICU admission and after fluid resuscitation of studied patients categorized according to survival.…”
Section: Discussionmentioning
confidence: 93%
“…administered, and none of both algorithms showed a good ability to predict fluid responsiveness and concluded that these results do not support the fluid responsiveness concept. These discrepancies concerning predictability of PVI to fluid responsiveness could be attributed to the fact that the concept is still recently involved in researches and not examined in wider scale comparative studies and to the variability of choice of the comparative cutoff point for PVI [23,36,37,40] and the choice of counter comparative method [36,37,40].…”
Section: Discussionmentioning
confidence: 99%